Ethanol’s Effect on Coq7 Expression in the Hippocampus of Mice - Zhou, Diana; Zhao, Yinghong; Hook, Michael; Zhao, Wenyuan; Starlard-Davenport, Athena; Cook, Melloni N.; Jones, Byron C.; Hamre, Kristin M.; Lu, Lu (Frontiers in Genetics, 2018)
Coenzyme Q (CoQ) is a well-studied molecule, present in every cell membrane in the body, best known for its roles as a mitochondrial electron transporter and a potent membrane anti-oxidant. Much of the previous work was done in vitro in yeast and more recent work has suggested that CoQ may have additional roles prompting calls for a re-assessment of its role using in vivo systems in mammals. Here we investigated the putative role of Coenzyme Q in ethanol-induced effects in vivo using BXD RI mice. We examined hippocampal expression of Coq7 in saline controls and after an acute ethanol treatment, noting enriched biologic processes and pathways following ethanol administration. We also identified 45 ethanol-related phenotypes that were significantly correlated with Coq7 expression, including six phenotypes related to conditioned taste aversion and ethanol preference. This analysis highlights the need for further investigation of Coq7 and related genes in vivo as well as previously unrecognized roles that it may play in the hippocampus.